A Novel Multipeptide Microarray for the Specific and Sensitive Mapping of Linear IgE-Binding Epitopes of Food Allergens - Kühne, Yvonne; Reese, Gerald; Ballmer-Weber, Barbara K.; Niggemann, Bodo; Hanschmann, Kay-Martin; Vieths, Stefan; Holzhauser, Thomas (International archives of allergy and immunology, 2015)
Background: The identification of B-cell epitopes of food allergens can possibly lead to novel diagnostic tools and therapeutic reagents for food allergy. We sought to develop a flexible, low-tech, cost-effective and reproducible multipeptide microarray for the research environment to enable large-scale screening of IgE epitopes of food allergens. Methods: Overlapping peptides (15-mer, 4 amino acid offset) covering the primary sequence of either peanut allergen Ara h 1 or all 3 subunits of the soybean allergen Gly m 5 were simultaneously synthesized in-house on a porous cellulose matrix. Identical peptide microarrays created with up to 384 duplicate peptide-cellulose microspots each were investigated for specificity and sensitivity in IgE immunodetection and in direct experimental comparison to the formerly established SPOT™ membrane technique. Results: The in-house microarray identified with 98% reproducibility the same IgE-binding peptides as the SPOT™ membrane technique. Additional IgE-binding peptides were identified using the microarray. While the sensitivity was increased between 2- and 20-fold, the amount of human serum required was reduced by at least two thirds over the SPOT™ membrane technique using the microarray. After subtraction of the potential background, we did not observe non-specific binding to the presented peptides on microarray. Conclusions: The novel peptide microarray allows simple and cost-effective screening for potential epitopes of large allergenic legume seed storage proteins, and it could be adapted for other food allergens as well, to study allergenic epitopes at the individual subject level in large paediatric and adult study groups of food allergic subjects.